2004
DOI: 10.1086/381877
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Hα Wings in the Symbiotic Stars AG Draconis and Z Andromedae

Abstract: We carried out polarimetric observations of two symbiotic stars, AG Dra and Z And, using the Line Polarimeter and Spectrograph (LIPS), a high-resolution echelle spectropolarimeter. We obtained the intrinsic polarization profiles with a broad wing in H for both symbiotics. Based on statistical analysis, we argue that the polarization profile of AG Dra is due to Raman scattering of Ly, because the characteristics of the polarization H profile agrees well with those of the Raman k6830 line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Lee & Yun 1998; Yoo, Bak & Lee 2002). This mechanism requires the presence of large H i column densities N H i ≳ 10 20 cm −2 , and has been observed to operate around symbiotic stars (Ikeda et al 2004), and potentially in close proximity to quasars (Lee & Yun 1998). In distant galaxies, however, these emission regions would be completely unresolved, and the polarization averages out to zero.…”
Section: Discussionmentioning
confidence: 99%
“…Lee & Yun 1998; Yoo, Bak & Lee 2002). This mechanism requires the presence of large H i column densities N H i ≳ 10 20 cm −2 , and has been observed to operate around symbiotic stars (Ikeda et al 2004), and potentially in close proximity to quasars (Lee & Yun 1998). In distant galaxies, however, these emission regions would be completely unresolved, and the polarization averages out to zero.…”
Section: Discussionmentioning
confidence: 99%
“…As a result we have to investigate other possibilities to identify the main source of radiation contributing to the broad Hα wings. For example, Ikeda et al (2004) found that the polarization profile of Hα does not agree with that of the Raman λ6830 line for Z And on 25/10/02 (i.e. during the 2002/03 brightening).…”
Section: Raman λ6825 and [Fe Vii] λ6087 Profilesmentioning
confidence: 99%
“…Ikeda et al (2004) performed linear spectropolarimetry around Hα of the two symbiotic stars Z And and AG Dra. No Raman‐scattered He ii features have been reported in these objects, and their analyses were confined to Hα wings and Raman‐scattered O vi 6825 and 7088.…”
Section: Discussion and Summarymentioning
confidence: 99%